Rebel rising eaudiobook A memoir. - Wilson, Rebel (Simon & Schuster Audio, 2024)
From the scene-stealing star of Pitch Perfect and Bridesmaids comes a "lively and reflective celebrity memoir seasoned with comedy and sincerity" ( Kirkus Reviews ) about Rebel Wilson's unconventional journey to Hollywood success and loving herself. This "beautiful, brave book," (Jenna Bush Hager, Today ) is the story of Rebel Wilson's remarkable personal transformation, from a painfully shy child in Australia who literally had to be dragged to drama classes to achieving breakout success in the US through iconic roles in Pitch Perfect , Bridesmaids , and Isn't It Romantic. Through "stunningly personal revelations" ( The New York Times ), Rebel shares the extraordinary experiences that shaped her life. A malaria-induced hallucination? An all-style martial arts fighting tournament? Junior handling at dog shows? And this was all BEFORE she moved to Hollywood! From her painful relationship with her father, weight gain and loss, a late-in-life sexual awakening, and fertility issues, Rebel shares her incredible journey to self-love in writing that is "frank and fun" (CBS Sunday Morning ). Rebel leads you through her hard-fought path to "making it," constantly questioning, "Am I good enough? Will I ever find love? Will I ever change and become healthy?" This extraordinarily entertaining memoir shows us how to love ourselves while making us laugh uncontrollably.